A novel 2-D coordination polymer with mixed azido and alkoxido bridges: Synthesis, structure and magnetic properties. (28th May 2015) - Stoicescu, Liliana; Maxim, Cătălin; Rouzières, Mathieu; Hillebrand, Mihaela; Clérac, Rodolphe; Andruh, Marius
Graphical abstract: A 2-D coordination polymer with a novel topology was synthesized: [Cu2 (L)(N3 )3 ] n (HL: 1, 5-diaminopentan-3-ol). The copper ions are connected by alkoxido and three types of azido bridges: single end-on (associated with the alkoxido bridge), double asymmetric end-on, and single asymmetric end-to-end. The magnetic investigation reveals a strong antiferromagnetic interaction between the copper ions. Abstract: A novel 2-D coordination polymer [Cu2 (L)(N3 )3 ] n 1 (HL: 1, 5-diaminopentan-3-ol) has been synthesized and its crystal structure and magnetic properties have been studied. The crystal structure of the compound1 consists of binuclear moieties [Cu2 (L)(N3 )3 ] with mixed alkoxido/end-on azido bridges, which are linked by double asymmetric end-on and single asymmetric end-to-end azido bridges, resulting in a 2-D layer extended within the ab crystallographic plane. Variable-temperature magnetic susceptibility data evidence strong antiferromagnetic interaction between the Cu II ions within the binuclear units, which are mediated by the two types of bridges ( J  = −123(2) cm −1, H  = −2 J S 1 S 2 ). The experimental value of the exchange coupling constant is confirmed by DFT calculations.